2013
DOI: 10.1093/nar/gkt402
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial disease-like symptoms caused by a reduced tRNA aminoacylation activity in flies

Abstract: The translation of genes encoded in the mitochondrial genome requires specific machinery that functions in the organelle. Among the many mutations linked to human disease that affect mitochondrial translation, several are localized to nuclear genes coding for mitochondrial aminoacyl-transfer RNA synthetases. The molecular significance of these mutations is poorly understood, but it is expected to be similar to that of the mutations affecting mitochondrial transfer RNAs. To better understand the molecular featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 67 publications
3
17
0
Order By: Relevance
“…Similar morphological aberrations have been observed in yeast, mammals, and D. melanogaster upon mutation of tRNA, tRNA synthesis, and other components of the mitochondrial translation system (Arbustini et al, 1998;Zick et al, 2009;Guitart et al, 2013). Thus, it is likely that the morphological changes observed in the tric1tric2 line are consequently due to the dynamic up-regulation of mitochondrial transcription and translation rates resulting from impaired tRNA uptake ability in tric1tric2 plants.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Similar morphological aberrations have been observed in yeast, mammals, and D. melanogaster upon mutation of tRNA, tRNA synthesis, and other components of the mitochondrial translation system (Arbustini et al, 1998;Zick et al, 2009;Guitart et al, 2013). Thus, it is likely that the morphological changes observed in the tric1tric2 line are consequently due to the dynamic up-regulation of mitochondrial transcription and translation rates resulting from impaired tRNA uptake ability in tric1tric2 plants.…”
Section: Discussionmentioning
confidence: 55%
“…The majority of mitochondria from tric1tric2 had cristae observable only at the periphery (45 of 64) and 11% of mitochondria had no observable cristae at all, while in Col-0, all mitochondria showed well-developed cristae crossing the entire organelle (Supplemental Table S1). The profound morphological changes, such as fewer cristae junctions and an enlarged swollen mitochondrion, had been observed previously in a variety of mutants in various species, commonly in mutants of transcription and translation components that display altered mitochondrial translation rates (Arbustini et al, 1998;Zick et al, 2009;Guitart et al, 2013). Vice versa, mutants to components involved in maintaining mitochondrial morphology, such as OpaI (an inner membrane protein involved in mitochondrial cristae formation), which are characterized by disorganized mitochondria with rounded cristae, interestingly exhibit increased mitochondrial translation levels (Cogliati et al, 2013).…”
Section: Tric1 and Tric2 Interact With Components Of The Tom And Tim mentioning
confidence: 79%
“…During the investigation of the function of Drosophila mitochondrial SerRS (DmSerRS2) (Guitart et al, 2010(Guitart et al, , 2013, we discovered SLIMP (CG31133; BcDNA: LD24627), a paralog of DmSerRS2 present in arthropods and echinoderms that retains a typical mitochondrial SerRS structure but has lost all tRNA aminoacylation activity (Guitart et al, 2010). We have reported that SLIMP depletion in vivo severely affects mitochondrial function, increases mtDNA levels, and is lethal at any stage of development (Guitart et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By silencing DmWARS2 we were able to demonstrate that such a partial reduction in aminoacylation was sufficient to severely affect fly development. Similarly, compromised ARS2 gene expression in flies has previously been shown to be able to model mitochondrial disease (Bayat et al, ; Guitart, Picchioni, Piñeyro, & Ribas de Pouplana, ; Meiklejohn et al, ).…”
Section: Discussionmentioning
confidence: 90%